IMPLEMENTASI QUALITY FUNCTION DEPLOYMENT (QFD) PADA MONOPOLE COFFEE LAB SURABAYA - Felita Liliana Soetjipto (CALYPTRA, 2017)
Abstract - Many choices coffee shop in Surabaya, especially in West Surabaya making the coffee shop owners are required to develop sustainable quality of their services in order to attract visitors, can compete and can also give satisfaction to the consumer. Efforts to improve the quality of service at the Monopole Coffee Lab research is conducted by applying Quality Function Deployment (QFD). The purpose of the implementation of the Quality Function Deployment (QFD) on services Monopole Coffee Lab is to get the Voice of the Customer, Priority Actions Technical Response, as well as produce a strategy proposal that should be taken by the company to improve the quality of service monopole Coffee Lab. Based on research conducted using Quality Function Deployment ( QFD ) , obtained 5 primary attributes and 24 secondary attributes and gained 9 attributes technical response. Based on House of Quality matrix , secondary attributes are a top priority for Monopole Coffee Lab to do repairs is Employees respond to the rapid response of visitors. From the calculation of technical response , it can be seen that the provide employee training. Keywords: Voice of Customer, Quality Function Deployment, House of Quality. Intisari - Banyaknya pilihan coffee shop di daerah Surabaya, tertama di Surabaya Barat sehingga membuat pemilik coffee shop dituntut berkelanjutan untuk mengembangkan kualitas layanan mereka dalam rangka untuk menarik pengunjung, dapat bersaing dan juga dapat memberi kepuasan kepada konsumen. Upaya peningkatan kualitas layanan pada Monopole Coffee Lab maka dilakukan penelitian dengan menerapkan Quality Function Deployment (QFD). Tujuan dari implementasi Quality Function Deployment (QFD) pada layanan Monopole Coffee Lab adalah untuk mendapatkan Voice of Customer, Prioritas Tindakan Respon Teknis, serta menghasilkan usulan strategi yang sebaiknya diambil oleh perusahaan untuk meningkatkan kualitas layanan Monopole Coffee Lab. Berdasarkan penelitian yang dilakukan menggunakan metode Quality Function Deployment (QFD), didapatkan 5 atribut primer dan 24 atribut sekunder serta diperoleh 9 atribut respon teknis. Berdasarkan matriks House of Quality, atribut sekunder yang menjadi prioritas utama bagi Monopole Coffee Lab untuk dilakukan perbaikan adalah karyawan cepat tanggap merespon pengunjung. Dari perhitungan respon teknis, dapat diketahui bahwa memberi pelatihan karyawan menjadi prioritas utama guna meningkatkan kualitas layanan Monopole Coffee Lab. Kata Kunci: Voice of Customer, Quality Function Deployment, House of Quality.